2018
DOI: 10.1136/bmjopen-2017-021242
|View full text |Cite
|
Sign up to set email alerts
|

Sipjeondaebo-tang in patients with breast cancer with fatigue: a protocol for a pilot, randomised, double-blind, placebo-controlled, cross-over trial

Abstract: IntroductionCancer-related fatigue is a frequent symptom in patients with cancer and one of the most distressing symptoms in patients with breast cancer. Sipjeondaebo-tang (Juzen-taiho-to in Japanese or Shi-Quan-Da-Bu-Tang in Chinese) is a widely used herbal medicine for the treatment of fatigue in Korea, China and Japan. The purpose of the present study is to evaluate the feasibility of Sipjeondaebo-tang for cancer-related fatigue.Methods and analysisThe present study is a randomised, double-blind, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Patients, the clinician, and the researcher in charge were blinded to treatment allocation. The patients were assigned to BCc1 nanomedicine and placebo groups based on the blocked randomization form [21].…”
Section: Methodsmentioning
confidence: 99%
“…Patients, the clinician, and the researcher in charge were blinded to treatment allocation. The patients were assigned to BCc1 nanomedicine and placebo groups based on the blocked randomization form [21].…”
Section: Methodsmentioning
confidence: 99%
“… 15 Furthermore, the effectiveness of SJDBT has been investigated for the management of cancer-related fatigue in women with breast cancer. 16 However, no clinical trials evaluating the efficacy of SJDBT in patients with CFS have been reported. Therefore, this study aimed to elucidate the effectiveness and safety of SJDBT granule administration for 8 weeks compared with placebo control for the management of fatigue severity in adult patients diagnosed with CFS by using the CDC criteria.…”
Section: Introductionmentioning
confidence: 99%
“…JTT has been used traditionally to treat fatigue, loss of appetite, and anorexia in patients with various diseases [7,8]. Various clinical and basic studies have indicated that JTT performs various pharmacological functions.…”
Section: Introductionmentioning
confidence: 99%